Micromechanics of piezoelectric fuzzy fiber-reinforced composite. (February 2015) - Dhala, Satyabrata; Ray, M.C.
Highlights: Effective properties of piezoelectric fuzzy fiber-reinforced composites are estimated. Micromechanics models are derived. Radially grown carbon nanotubes significantly improve the in-plane piezoelectric properties. Abstract: A novel continuous unidirectional piezoelectric fuzzy fiber reinforced composite (PFFRC) comprised of zig-zag single-walled carbon nanotubes and piezoelectric fibers as reinforcements embedded in a conventional polymer matrix has been studied. Effective piezoelectric and elastic properties of this composite have been determined by the method of cell (MOC) approach and the Mori–Tanaka (MT) method. It is found that the effective in-plane piezoelectric coefficient and elastic coefficients of the PFFRC are significantly improved over those of the existing 1–3 piezoelectric composite without reinforced with carbon nanotubes.